(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The manufacture of curved wooden details is a technological process with long duration. Repeatedly reducing the time needed for plasticizing and drying the wood may be performed by its high-frequency heating. The basic regime parameters that control the production of curved detail in high frequency electromagnetic field are: the frequency of the electricity (respectively of the field power), the water content in the material, the duration of the process (plasticizing, bending and stabilization), the relationship between the anode and grid current (Ip/Ia). Drawing up a regime for faultless performance of the operation is a difficult task with multiple alternatives. However, there are insufficient data and research upon that issue, especially for a comprehensive regime including consistent implementation of the phases of plastification, bending and drying of wood. In this connection, some regimes of high frequency plasticizing, bending and drying were carried based on beech details. The conducted regimes were assessed by the duration of the production cycle and the final production waste.